Weak signals and wild cards: a prospective look at intellectual production - Jesús Mujica-Pérez (Universidad Central de Venezuela, 2020)
This study aims to determine the ecology surrounding intellectual production in the Postgraduate program in Research and Development Management at the Central University of Venezuela during the 2019 – 2020 period, through a prospective tool known as weak signals and wild cards. Counting on the participation of 20 students from the postgraduate chair in Prospective, it was based on hermeneutical ethnomethodology, in which a qualitative, instrumental approach was undertaken. In this approach, brainstorming, structured surveys, group discussions using STEEPV and World Coffee dynamics, and mainly online documentation were used. Fifty-five signals (19 positive and 36 negative) were detected; all of them associated with interest in research and development in the Venezuelan society. Some of the most relevant signals are those related to a huge growth of digital businesses through the 4.0 application, a considerable migration of professionals, limited Internet access, and economic difficulty to purchase updated software; in addition to the impact of changing rectors, constant conflict between authorities and the government, among others. Keywords: Wild cards; weak signals; prospective; STEEPV; World coffee